Application of Big Data Technology in LKJ Equipment Analysis System - YANG Xian; YAN Sheng (Kongzhi Yu Xinxi Jishu)
At present, there are some problems in LKJ equipment analysis system, such as incomplete analysis, low efficiency and difficult fault location. This paper analyzed the future development requirements of LKJ equipment analysis system and the application of big data technology, and proposed a scheme of LKJ equipment analysis system based on big data technology. Based on the big data platform, it uses continuous variable mutation, correlation coefficient method, complex relationship network and other analysis methods to mine and analyze a large number of historical data of LKJ equipments, forming abnormal data and key fault causes of LKJ equipments and support. The application of big data technology can provide data support and decision guidance for problem finding in time, fault analysis and maintenance of LKJ equipments.